El método Decroly y la lecto-escritura en el tercer grado “D” de la escuela de educación básica “Alonso de Mercadillo”. Periodo 2021-2022. - Peña Sánchez, Maryuri Viviana (2022)
The research entitled; the Decroly method and reading and writing in the third grade, "D", of the School of Basic Education, "Alonso de Mercadillo", Period 2021-2022. The general objective of the study is to determine the influence of the Decroly method in the learning process of reading and writing of children in the third parallel grade "D" of the School of Basic Education "Alonso de Mercadillo", as specific objectives; to diagnose the process of learning to read and write of the children of third grade parallel "D", to plan and execute a plan of improvement of the learning of reading and writing through the use of the Decroly method for the children of third grade parallel "D" and finally to evaluate the influence of the Decroly method in the process of learning to read and write of the children of third grade parallel "D"; the variables investigated were the Decroly method and reading and writing, in the investigative process the following methods were used: scientific, descriptive, analytical, analytical, analytical and scientific: scientific, descriptive, analytical, synthetic, statistical, qualitative, quantitative and inductive; the research was descriptive with a mixed approach and non-experimental design, to gather the necessary information, the teacher was interviewed and the children were given a Magallanes literacy assessment test; the results obtained allowed determining the errors made by the students when reading and writing and the levels of comprehensive reading; to support the strengthening of literacy, an alternative proposal was designed called ¨Con Decroly: Leo, Escribo, Aprendo y me divierto¨ (With Decroly: I read, I write, I learn and I have fun), aimed at improving the learning of reading and writing, was designed and implemented through classroom activities that were satisfactorily executed. Therefore, it is concluded that the Decroly method, which is based on observation and experimentation on the natural way of spontaneous learning of children, is an effective methodological strategy for strengthening literacy. Key words: Decroly method, literacy, teaching-learning.